2019
DOI: 10.1371/journal.ppat.1007608
|View full text |Cite
|
Sign up to set email alerts
|

A poxvirus pseudokinase represses viral DNA replication via a pathway antagonized by its paralog kinase

Abstract: Poxviruses employ sophisticated, but incompletely understood, signaling pathways that engage cellular defense mechanisms and simultaneously ensure viral factors are modulated properly. For example, the vaccinia B1 protein kinase plays a vital role in inactivating the cellular antiviral factor BAF, and likely orchestrates other pathways as well. In this study, we utilized experimental evolution of a B1 deletion virus to perform an unbiased search for suppressor mutations and identify novel pathways involving B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 80 publications
(113 reference statements)
2
32
0
Order By: Relevance
“…Outside of these notable pseudoenzyme families, relatively few examples of competitor and/or "decoy" pseudoenzymes have been identified to date. However, new data confirm their expansion within plant, fungal, and pathogen proteomes (24-27), including, for example, a new viral pseudoenzyme that provides the pathogen with an advantage by directly competing with host cell defense mechanisms (28).…”
Section: Class Function Examples Referencesmentioning
confidence: 96%
“…Outside of these notable pseudoenzyme families, relatively few examples of competitor and/or "decoy" pseudoenzymes have been identified to date. However, new data confirm their expansion within plant, fungal, and pathogen proteomes (24-27), including, for example, a new viral pseudoenzyme that provides the pathogen with an advantage by directly competing with host cell defense mechanisms (28).…”
Section: Class Function Examples Referencesmentioning
confidence: 96%
“…The precise function of vaccinia virus B12 during infection has remained enigmatic to date. Specifically, previous studies of a B12 deletion mutant, lacking 83% of the B12R gene, revealed that this B12 deletion virus replicated efficiently in cultured cells and in vivo (26); however, when B12 was deleted in the context of the vaccinia virus B1 deletion mutant ΔB1mutB12, B12 was revealed to be repressive to vaccinia virus replication (6). Considering this evidence that B12 acts as a repressor of vaccinia virus replication upon loss of B1, we sought to determine whether the requirement of vaccinia virus for either vaccinia virus B1 or the cellular kinase VRK2 is functionally linked to vaccinia virus B12.…”
mentioning
confidence: 97%
“…The vaccinia virus B1 kinase is expressed early during infection and promotes multiple facets of the vaccinia virus life cycle (6)(7)(8)(9)(10)(11). Genetic and biochemical investigations of the B1 kinase using temperature-sensitive viruses (7,9,(12)(13)(14) and a B1 deletion mutant virus (6,15) have provided insights into the essential roles played by B1 during vaccinia virus infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations